HOUT-19. DEVELOPMENT OF A NOVEL BURDEN SURVEY FOR CAREGIVERS OF GLIOBLASTOMA MULTIFORME (GBM) PATIENTS. (6th November 2017) - Au, Trang; Bauer, Hillevi; Ma, Junjie; Nelson, Ryan; Watanabe, Alexandre; Singh, Prianka; Korytowsky, Beata; Wilson, Elizabeth; Willmarth, Nicole; Cohen, Adam; Colman, Howard; Stenehjem, David; et al.
Abstract: BACKGROUND: Glioblastoma multiforme (GBM) is an incurable brain cancer associated with a grim prognosis. Afflicted individuals often experience rapid decline in cognitive function, with implications on quality of life and support systems. Although the complexity of GBM to patients has been reported, less is known about its impact on caregivers. We developed a survey tool to evaluate caregiver experience with an emphasis on caregiver burden. METHODS: A literature review of caregiver studies in other cancers, Alzheimer's disease, and dementia was conducted. A preliminary survey was drafted followed by consultation with neuro-oncologists and patient advocates to further define relevant domains and questions. Next, we conducted individual caregiver interviews with a random convenience sample of 10 self-identifying primary caregivers of adult patients receiving care for GBM at Huntsman Cancer Institute, Salt Lake City, Utah. Caregivers were asked to review the survey from their perspective; specifically to rank domains, identify aspects of caregiving currently absent from the survey, and provide input on questions to be eliminated. RESULTS: Five domains related to caregiver burden were identified: 1) emotional health of caregiver; 2) change in cognitive function of loved one with GBM; 3) information needs; 4) caregiver tasks; and 5) medical/non-medical caregiver burden. Although caregivers reported all domains were important, "Emotional health of caregiver" was voted as the most important domain and "Information needs" was ranked last. The survey will be refined with findings from caregiver interviews, including new areas of interest, i.e. relationship impact, travel logistics, and reality of living "scan to scan". Further, consultation with a psychometrician will ensure the survey is an appropriate tool to measure caregiver burden, after which a pilot of the survey will be conducted before final dissemination. CONCLUSIONS: Direct caregiver feedback provides valuable insight towards development and validation of a survey tool to measure caregiver burden in GBM.